Varying Impressions. Issue 1 (January 2015) - DAVIES, DAVID; Mag Uidhir, Christy; Freeland, Cynthia
Abstract My aim in this article is to locate various forms of printmaking in a broader framework for thinking about so‐called 'multiple' artworks, artworks that, as this is normally put, admit of multiple instances. I first sketch a general framework for the philosophical exploration of multiple artworks and the philosophical issues to which they give rise. I then address certain forms of printmaking that might be thought to generate singular rather than multiple artworks. Next, I look at how those print works that are multiples stand in relation to other multiple works of the same general type in respect of certain challenges relating to the repeatability and variability of works. Finally, I examine a further question—the problem of limitation—more specific to prints qua multiples.